Pengaruh kepuasan konsumen dan nilai yang dirasakan terhadap loyalitas konsumen dengan kepercayaan konsumen sebagai variabel intervening pada skincare MS Glow - Nur Hafidhah Syahna; Marwan Marwan (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study analyzes how customer trust affects value, loyalty, and satisfaction with MS Glow skin care products. The researchers deliberately selected 100 students from Padang State University who had repeatedly purchased MS Glow skin care products for this study. The data was analyzed using SEM-PLS 4.0. The study shows that customer satisfaction and perceived value do not influence customer loyalty. Trust in the company significantly influences customer loyalty. Consumer trust does not influence satisfaction or value. With consumer trust as a mediator, customer satisfaction has a small influence on customer loyalty. Trust moderates the relationship between perceived value and customer loyalty. These findings indicate that the role of consumer trust in shaping customer loyalty is contextual among Padang State University students who use local skincare products, namely MS Glow, thereby broadening the understanding of consumer behavior theory in products with specific levels of involvement and perceived risk.